Normal-Appearing Salivary Gland Ultrasonography Identifies a Milder Phenotype of Primary Sjögren's Syndrome - Zandonella Callegher, Sara; Zabotti, Alen; Giovannini, Ivan; Treppo, Elena; Quartuccio, Luca; De Vita, Salvatore (Frontiers in Medicine, 2020)
Objective. Salivary gland ultrasound (SGUS) is emerging as a valid tool in the management of primary Sjögren’s syndrome (pSS). This study aimed to investigate whether pSS patients with normal-appearing or pathological SGUS findings showed different clinical, laboratory, and pathologic pSS-related features, and to compare the results by using two different SGUS scores. Methods. Consecutive pSS patients, according to the ACR-EULAR classification criteria, were evaluated. Salivary glands were scored using the early 1992 score by De Vita et al. and the latest 2019 OMERACT score, both being semiquantitative 0-3 scoring systems focused on ultrasonographic parenchymal inhomogeneity (grade 0 and 1 normal-appearing; grade 2 and 3 pathological). The patients were then divided into two groups: “SGUS normal-appearing” if all the salivary glands had normal-appearing parenchyma (grade 0 or 1), or “SGUS pathological” if the grade was 2 or 3 in at least one salivary gland. The associations between SGUS and pSS-related clinical, laboratory, and pathological features were then investigated in the two groups. Results. One hundred pSS patients were evaluated, the mean age (±SD) was 60.9 ±12.0 years, and mean disease duration was 11.7 ±7.2 years. Twenty-nine out of 100 (29%) patients were in the “SGUS normal-appearing” group and 71/100 (71%) in the “SGUS pathological” group. A normal-appearing SGUS was significantly associated with the absence of anti-La/SSB antibodies (p<0.001) and normal unstimulated salivary flow rate (p=0.02) by both univariate and multivariate analyses. By univariate analysis, a normal-appearing SGUS was significantly associated also with the absence of rheumatoid factor (p=0.002) and of serum monoclonal component (p=0.003), ESSDAI <5 (p=0.03), and with a negative lip biopsy (p=0.029). No associations were found with other items, including anti-Ro/SSA (p=0.145), Schirmer’s test (p=0.793), ESSPRI (p=0.47), and demographic data. No differences in these results were observed by using the two SGUS scoring systems. Conclusion. The SGUS allowed to identify different phenotypes of pSS, and different SGUS scores focused on salivary gland inhomogeneity may be effective to this end.